2019
DOI: 10.1016/j.celrep.2019.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Robust Control of a Brain-Persisting Parasite through MHC I Presentation by Infected Neurons

Abstract: Highlights d A model of resistance to T. gondii encephalitis in C57BL/6 mice d Efficient MHC I presentation of tachyzoite antigens controls CNS parasites d Efficient MHC I presentation of tachyzoite antigens limits CNS inflammation d Neuronal MHC I presentation is required for chronic control of brain parasite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 71 publications
2
52
0
2
Order By: Relevance
“…Collectively, these data are consistent with prior work showing upregulated inflammatory pathways and an increase in immune cell infiltration in the CNS during infection ( 49 52 ). Our identification of immune cell transcripts within our “neuron” transcriptomes and visualization of CD3 + T cells suggest our samples contain transcripts from nonneuronal cells, such as CD8 + T cells, that may be in extreme proximity to the isolated neurons.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Collectively, these data are consistent with prior work showing upregulated inflammatory pathways and an increase in immune cell infiltration in the CNS during infection ( 49 52 ). Our identification of immune cell transcripts within our “neuron” transcriptomes and visualization of CD3 + T cells suggest our samples contain transcripts from nonneuronal cells, such as CD8 + T cells, that may be in extreme proximity to the isolated neurons.…”
Section: Resultssupporting
confidence: 92%
“…We chose to use type II-infected mice because the transcripts from type II TINs showed the highest level of T cell contamination ( Fig. 4B) and recent elegant work by the Blanchard lab has indirectly suggested that CD8 ϩ T cells interact with neurons infected with type II parasites in vivo (49). To evaluate the distance between T cells and TINs or Bystander neurons, 200-m-thick (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data are consistent with previous work which has shown upregulated inflammatory pathways and an increase in immune cell infiltrate during infection [48][49][50][51] . Our identification of immune cell transcripts within our "neuron" transcriptomes suggest our samples contain transcripts from nonneuronal cells, such as CD8 + T cells, that were in extremely close proximity to the isolated neurons.…”
Section: Bystanderssupporting
confidence: 93%
“…6). While future work will focus on distinguishing between these possibilities, either model adds to the growing literature that, contrary to dogma, infected neurons have robust immune responses to microbes and cytokines and can present antigens to T cells in vivo 7,59,50 .…”
Section: Especially Cd8 T Cells Hone-in On Tinsmentioning
confidence: 99%